(untitled) (Nativa, 2024)
ABSTRACT: This study aims to measure the sanitation water quality index towards the SDG target in the socio-economic field. The difficulties faced by urban communities in obtaining sanitation water needs, and the quality of water used by the community from dug well water sources with ineffective management so that it is necessary to maintain the importance of groundwater supply sources. The method used was descriptive quantitative with laboratory tests of sanitation water quality based on the Regulation of the Ministry of Health of the Republic of Indonesia in 2017 and 2023 to determine the water quality index, surveys, and questionnaires. The research location was in Bandung City, West Java, Indonesia. 24 points of the research location were conducted to collect data from 400 respondents. The time in this study is 2022-2024. The results showed that the WQI of 24 samples of water quality status values for sanitation differ. Permenkes RI number 2 of 2023 has a higher value than Permenkes RI number 32 of 2017. Therefore, based on these findings, the socio-economics of residents in densely populated urban settlements impacts the environment, especially water quality. Keywords: dense settlement; sanitation; water supply. Quantificação do índice de qualidade da água sanitária e do progresso em direção às metas dos ODS na área sócio-econômica RESUMO: Este estudo tem como objetivo medir o índice de qualidade da água de saneamento em direção à meta dos ODS no campo socio-econômico. As dificuldades enfrentadas pelas comunidades urbanas na obtenção das necessidades de água para saneamento e a qualidade da água utilizada por essas comunidades proveniente de fontes de água de poços escavados com gestão ineficaz de modo que é necessário manter a importância das fontes de abastecimento de água subterrânea. O método utilizado foi quantitativo descritivo com testes laboratoriais da qualidade da água de saneamento com base no Regulamento do Ministério da Saúde da República da Indonésia, entre 2017 e 2023, visando determinar o índice de qualidade da água, além do emprego de questionários. O local da investigação foi na cidade de Bandung, Java Ocidental, Indonésia. Foram avaliados 24 pontos de amostragens, com dados de 400 entrevistados, no período de 2022 a 2024. Os resultados mostraram que o WQI de 24 amostras do índice de qualidade da água foram diferentes. Permenkes RI número 2 de 2023 apresentou valor mais alto em comparação com Permenkes RI número 32 de 2017. Portanto, com base nesses resultados, a socioeconomia dos residentes em assentamentos urbanos densamente povoados tem um impacto no meio ambiente, especialmente na qualidade da água. Palavras-chave: povoamento denso; saneamento; abastecimento de água.